2009
DOI: 10.1093/bja/aep209
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ramosetron with ondansetron for prevention of postoperative nausea and vomiting in patients undergoing gynaecological surgery

Abstract: Ramosetron 0.3 mg i.v. was as effective as ondansetron 8 mg i.v. in decreasing the incidence of PONV and reducing nausea severity in female patients during the first 24 h after gynaecological surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 19 publications
8
70
1
Order By: Relevance
“…[13] Headache and dizziness are the most common side effects of 5 HT-3 receptor antagonists. [14] No statistically significant difference was found in the incidence of adverse effects in both groups in our study which is similar as found by Fujji et al [13] and Kim et al [15] In conclusion, both Ondansetron and Granisetron were equally effective on preventing PONV in early postoperative period in patients undergoing gynaecological surgery under spinal anesthesia. In the late postoperative period, however, Granisetron was better with lessincidence of PONV and less need for rescue antiemetic.…”
Section: Resultssupporting
confidence: 89%
“…[13] Headache and dizziness are the most common side effects of 5 HT-3 receptor antagonists. [14] No statistically significant difference was found in the incidence of adverse effects in both groups in our study which is similar as found by Fujji et al [13] and Kim et al [15] In conclusion, both Ondansetron and Granisetron were equally effective on preventing PONV in early postoperative period in patients undergoing gynaecological surgery under spinal anesthesia. In the late postoperative period, however, Granisetron was better with lessincidence of PONV and less need for rescue antiemetic.…”
Section: Resultssupporting
confidence: 89%
“…There are several reports that Ramosetron was as effective as or even more effective than the older 5-HT3 receptor for the prevention of PONV during 0-24 h after anaesthesia (Kim SI, et al). [17] Furthermore, the antiemetic effect of Ramosetron can last up to 48 hours (Fujii Y et al). [18] The differences in effectiveness between the older 5-HT3 receptor antagonist and Ramosetron may be related to the longer elimination half-life and higher receptor affinity (pKi=8.5) of Ramosetron.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Kim et al demonstrated that ramosetron 0.3 mg was effective as ondansetron 8 mg, given i.v. before induction of anesthesia, in reducing the incidence of PONV [44].…”
Section: Yoshitaka Fujiimentioning
confidence: 99%